Immune response costs are associated with changes in resource acquisition and not resource reallocation. (27th January 2014) - Bashir‐Tanoli, Sumayia; Tinsley, Matthew C.; Moore, Ignacio
Summary Evolutionary ecologists frequently argue that parasite defence is costly because resources must be reallocated from other life‐history traits to fuel the immune response. However, this hypothesis is rarely explicitly tested. An alternative possibility is that immune responses impair an organism's ability to acquire the resources it needs to support metabolism. Here, we disentangle these opposing hypotheses for why the activation costs of parasite resistance arise. We studied fecundity costs associated with immune stimulation in Drosophila melanogaster. Then, by measuring correlated changes in metabolic rate, food consumption and body weight, we assessed whether responses were consistent with immunity costs originating from altered resource allocation or from impaired resource acquisition. Microbial injection resulted in a 45% fecundity decrease. It also triggered a mean decline in metabolic rate of 6% and a mean reduction in food intake of 31%; body weight was unaffected. Metabolic rate downregulation was greater in males than in females, whereas declines in food ingestion were of similar magnitude in both sexes. These physiological shifts did not depend on whether microbial challenges were alive or dead, thus they resulted from immune system activation not pathogenesis. These costs of immune activation are significant for individuals that successfully resist infection and might also occur in other situations when immune responses are upregulated without infection. Whilst we found significant activation costs of resistance, our data provide no compelling evidence for the popularly argued hypothesis that immune deployment is costly because of reallocation of energetic resources to the immune system. Instead, reduction in resource acquisition due to 'infection‐induced anorexia' may be the principal driver of metabolic changes and fecundity costs resulting from immune response activation.